DAMPAK PENGGUNAAN MEDIA SOSIAL TIKTOK PADA KARAKTER SOPAN SANTUN PESERTA DIDIK KELAS V SDN SIDOREJO 02 KECAMATAN BENDOSARI KABUPATEN SUKOHARJO (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to describe the impact of TikTok social media usage on the politeness character of elementary school students. The rapid development of digital technology has made social media, especially TikTok, widely used by children, which can influence their behavior and character. This research employed a descriptive qualitative approach conducted at SDN Sidorejo 02, Bendosari District, Sukoharjo Regency. The subjects of this study included the principal, teachers, and fifth-grade students selected purposively. Data were collected through observation, interviews, and documentation, and validated using triangulation techniques. The data were analyzed through data reduction, data display, and conclusion drawing. The results showed that TikTok usage has both positive and negative impacts on students’ politeness character. The positive impacts include increased self-confidence and better self-expression in social interactions. However, the negative impacts include the use of impolite language, decreased respect towards teachers and parents, and the tendency to imitate inappropriate behaviors from online content. These findings indicate that social media plays a significant role in shaping students’ character, thus requiring proper supervision and guidance from parents and teachers. Therefore, it is important to direct the use of TikTok wisely in order to support positive character development among students.